2021
DOI: 10.1097/fbp.0000000000000666
|View full text |Cite
|
Sign up to set email alerts
|

The effects of subchronic agmatine on passive avoidance memory, anxiety-like behavior and hippocampal Akt/GSK-3β in mice

Abstract: Agmatine, a polyamine derived from l-arginine, has been suggested to modulate memory. However, the available evidence regarding the effect of agmatine on the memory of intact animals is contradictory. This study aimed to assess the dose–response effect of subchronic agmatine on passive avoidance memory and anxiety-like parameters of elevated plus maze in adult intact mice. Furthermore, considering the roles of Akt/GSK-3β signaling pathway in memory and Alzheimer’s disease, the hippocampal contents of phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
2
2
0
Order By: Relevance
“…Consistent with our results, Ostovan et al. (2022) indicated that high doses of agmatine can improve memory. Therefore, agmatine might provide neuroprotective utility against cognitive impairments induced by PS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our results, Ostovan et al. (2022) indicated that high doses of agmatine can improve memory. Therefore, agmatine might provide neuroprotective utility against cognitive impairments induced by PS.…”
Section: Discussionsupporting
confidence: 93%
“…further showed that agmatine improved memory impairment caused by PS in the male offspring. Consistent with our results,Ostovan et al (2022) indicated that high doses of agmatine can improve memory. Therefore, agmatine might provide neuroprotective utility against cognitive impairments induced by PS.In our study, BDNF level expression was significantly enhanced in the VTA of offspring of mothers exposed to psychological stress when compared to the levels in the control group, and this level wasF I G U R E 5 Assessment of the passive avoidance learning and memory in shuttle box: (a) shock number and (b) step-through latency.…”
supporting
confidence: 92%
“…Additionally, NOR is more comparable to the tests used to evaluate human cognition, which increases the ecological validity of this test in comparison to the other animal memory tasks (Lueptow, 2017). Although there are studies indicating that sub-chronic treatment with agmatine (for periods of 10 days or more) has a dose-dependent effect on memory, accordingly a dose of 10 mg/kg was even shown to impair memory (Farokhi et al ., 2022; Os tovan et al ., 2022), i n sho rter periods, the memory-damaging effect of agmatine in doses of 5 and 10 mg has not been observed (Zarifkar et al ., 2010). T heref ore, in general, it seems that agmatine at a dose of 10 mg/kg does not have pro-cognitive effects that can counteract the deleterious effects of Al-NP on memory.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the streptozotocin-induced memory impairment model, the neuroprotective effect of agmatine was accompanied by an increase in hippocampal GSK-3β phosphorylation (Moosavi et al ., 2014b). In intact animals, sub-chronic administration of agmatine increases hippocampal GSK-3β phosphorylation in addition to its antidepressant and memory-enhancing effects (Freitas et al ., 2014; Ostovan et al ., 2022). Considering the pathological role of GSK-3β in memory disorders, modulation of this kinase by agmatine may play a role in the protective effect of this polyamine against Al-NP.…”
Section: Discussionmentioning
confidence: 99%